2021
DOI: 10.1016/j.preteyeres.2020.100917
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous outflow regulation – 21st century concepts

Abstract: We propose an integrated model of aqueous outflow control that employs a pump-conduit system in this article. Our model exploits accepted physiologic regulatory mechanisms such as those of the arterial, venous, and lymphatic systems. Here, we also provide a framework for developing novel diagnostic and therapeutic strategies to improve glaucoma patient care. In the model, the trabecular meshwork distends and recoils in response to continuous physiologic IOP transients like the ocular pulse, blinking, and eye m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 191 publications
1
84
0
Order By: Relevance
“…Our study as well as prior viscoelastic studies demonstrate disruption of valvular structure traversing the SC lumen and their attachments at CC entrances. We hypothesize that disruption of connections between the TM and CC entrances reduces the ability of the CC entrances to move in response to pressure-dependent TM motion [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study as well as prior viscoelastic studies demonstrate disruption of valvular structure traversing the SC lumen and their attachments at CC entrances. We hypothesize that disruption of connections between the TM and CC entrances reduces the ability of the CC entrances to move in response to pressure-dependent TM motion [5].…”
Section: Discussionmentioning
confidence: 99%
“…SC functions as a compressible chamber. Its morphology and behavior suggests that it is a component of a lymphatic-like pump that regulates IOP [5]. Many studies and multiple lines of evidence document that flow to the aqueous veins is pulsatile and that the origin of the aqueous inducing pulsatile flow is SC and the distal outflow channels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…TM distension into SC forces aqueous into collector channels (CC) entrances and aqueous veins. As the pressure spike decays, the TM lamellae return to their original configuration with a resultant reduction of SC pressure, permitting aqueous flow into the canal [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…TM biomechanics determine TM stiffness and the ability to induce pumplike pulsatile flow [11][12][13][14]. Clinical and laboratory evidence has shown that the pulsatile pattern of aqueous flow decreases and even stops in advanced glaucoma, thought to result from increased TM stiffness [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The immunological targeting of the β 2 -AR is the basis for the hypothesis of an involvement of β 2 -agAAbs in dysregulation of IOP (Zimmerman, 1977). The IOP is the result of production (ciliary body) and outflow (trabecular meshwork, uveosclera) of the aqueous humor (Johnstone et al, 2020;Kaufman, 2020;Sunderland and Sapra, 2021). Clinical data of patients with POAG, showing a reduced IOP after removal of all circulating IgG antibodies by immunoadsorption, support this hypothesis (Junemann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%